Dynamin 2 mutations in Charcot-Marie-Tooth neuropathy highlight the importance of clathrin-mediated endocytosis in myelination - Sidiropoulos, Páris; Kuner, Rohini (Brain, 2012)
Abstract. Mutations in dynamin 2 (DNM2) lead to dominant intermediate Charcot-Marie-Tooth neuropathy type B, while a different set of DNM2 mutations cause auto